The nature of the symptom psychosomatic, affecting football players in sports competitions - djamel zehar (sports creativity, 2025)
Football is the most popular game in the world because of the simplicity and ease of application of its principles, but it is characterized by a set of requirements that we can not find in other sports among these requirements, we find the psychological requirements that the player should be called before or during sports competition The appearance of some psychological symptoms - such as (tension - anxiety - arousal - muscle twitching - stomach upset and digestion ...). These symptoms indicate the level of pre - competition situation, where the player passes before the actual participation in the tournament a state called psychologists In pre-competition mode, which is characterized by psychological manifestations that affect the level of play. Therefore, we have studied this phenomenon, because of the importance of the psychological side, which should not be overlooked, because of the character of football stadiums concerned tension ... which may have a direct and negative impact on the level of performance of the football player and the above is clear to us the importance of this study where psychosomatic play a significant role in the behavior and responses of the players. So we find countries racing in all areas, especially in the field of sports activity or try all countries to follow the scientific method at the beginning and the search to reach the individual sports to the highest levels, especially in terms of psychological preparation of players and for the development and development of qualities and psychological features and Here are the psychological factors associated with sports competitions that affect significantly and clearly at the level of athletes. What is the nature of the symptoms of the psychosomatic? Does psychological anxiety play a role? And do these symptoms affect the performance of football players ?. In this study, we tried to focus on the field aspect, and this is according to the nature of the researcwhich depends on the field in the first place and we will discuss some elements, including the curriculum, the sample, the study tools, as well as some of the results reached The results of this study were based on a set of necessary results. In general, the study showed that the study had significant sexosomatic symptoms before the sports competition. The nature of these symptoms was: aggressive behavior, involuntary urination, anxiety, increased heartbeat, sweating Therefore, these symptoms have a prominent and clear effect on the performance of the player during the competition and therefore anxiety plays a key role in the emergence of these symptoms in the player. It is necessary to include the academic psychological preparation and make it part of the general and integrated preparation for athletes and sports teams and apply it strictly in the short and long term. The need to encourage psychologists in sports and to include them in teams as assistants and trainers in terms of psychological follow-up of players, which starts from the first stages of the year in order to achieve future goals. The need to sensitize players to the relationship between body and mind and its importance to performance, and then teach them and gain the psychological skills necessary to deal with the physiological and mental experiences through which they can deal with the pressures of competition and mental energy control, and then become the responsibility of the player to recruit during the game